FORMATION OF NOMENCLATURE OF QUALITY INDICATORS FOR DESIGN OF DANCE SMART CLOTHES - POLUCHOVICH, IRYNA; ZAKHARKEVICH, OKSANA; LISENKO, SERGII (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Today, due to the rapid development of distance learning, there is a problem with the quality of education, including physical. Analysis of the level of injuries in choreography and gymnastics showed a high percentage of injuries to the lower extremities. To minimize the number of injuries and increase the professionality of dancers, developing a smart-clothing for dancing is necessary. Preliminary analysis of smart technologies in sports confirmed the need to use smart technologies to read and monitor the physical data of athletes during training. Still, it showed the absence of such technologies in dance. The advisability of research of smart technologies and the development of smart costume for dancing with additional functional properties is confirmed. An analysis of the requirements for dancing smart clothes there. Based on the analysis of dance and smart clothing requirements, a list of quality indicators for designing dance smart clothing was developed for further evaluation to determine a set of essential quality indicators for designing stage and training dance smart clothing.
Keywords: smart textile; dance costume; smart technologies; nomenclature; requirements